Evaluation of the Nelson Criteria as an Indicator for Nonsurgical Admission in Trauma Patients. Issue 7 (July 2022) - Lee, Janet S.; Khan, Abid D.; Schlitzkus, Lisa; Schmoekel, Nathan; Stassinopoulos, Jerry; Brockman, Valerie; Schroeppel, Thomas J.
Geriatric patients with complex medical comorbidities who sustain minor injuries may warrant admission to nonsurgical services. The Nelson score provides an objective scoring system that helps identify patients appropriate for nonsurgical admission (NSA). The purpose of this study is to assess the utility of the Nelson criteria in determining the most appropriate admission service. A retrospective review was performed on patients ≥65 years admitted from 12/2016 to 11/2020. 2410 patients met the inclusion criteria. Patients with Nelson score ≥6 were older with more comorbidities, had a lower injury severity score (7.5 vs 12.5, p<0.0001), and a higher rate of NSA (29.2% vs 12.7%, p<0.0001) compared to patients with Nelson score <6. On the multivariable logistic regression, admission service was not identified as an independent predictor of mortality. Utilizing the Nelson criteria may provide an objective measure to stratify and identify patients who would benefit from NSA.